Advanced Electrical Circuit Analysis Practice Problems, Methods, and Solutions - Rahmani-Andebili, Mehdi; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This study guide is designed for students taking advanced courses in electrical circuit analysis. The book includes examples, questions, and exercises that will help electrical engineering students to review and sharpen their knowledge of the subject and enhance their performance in the classroom. Offering detailed solutions, multiple methods for solving problems, and clear explanations of concepts, this hands-on guide will improve student$1 (Bs problem-solving skills and basic understanding of the topics covered in electric circuit analysis courses. Exercises cover a wide selection of basic and advanced questions and problem; Categorizes and orders the problems based on difficulty level, hence suitable for both knowledgeable and under-prepared students; Provides detailed and instructor-recommended solutions and methods, along with clear explanations; Can be used along with the core textbooks. .s
Problems: Graph Theory and Network Topology, Application of Graph Theory in Electrical Circuit Analysis, and Principle of Duality -- Solutions of Problems: Graph Theory and Network Topology, Application of Graph Theory in Electrical Circuit Analysis, and Principle of Duality -- Problems: State Equations of Electrical Circuits -- Solutions of Problems: State Equations of Electrical Circuits -- Problems: Laplace Transform and Network Function -- Solutions of Problems: Laplace Transform and Network Function -- Problems: Natural Frequencies of Electrical Circuits -- Solutions of Problems: Natural Frequencies of Electrical Circuits -- Problems: Network Theorems -- Solutions of Problems: Network Theorems -- Problems: Two-Port Networks -- Solutions of Problems: Two-Port Networks -- Problems: Nonlinear Electrical Circuits, Operational Amplifier, Convolution Integral -- Solutions of Problems: Nonlinear Electrical Circuits, Operational Amplifier, Convolution Integral.
Keywords: Electronic circuits; Cooperating objects (Computer systems).; Technical education; Electronic Circuits and Systems; Cyber-Physical Systems; Engineering and Technology Education; Electric circuit analysis; Electric circuits -- Testing